2017
DOI: 10.1111/jog.13518
|View full text |Cite
|
Sign up to set email alerts
|

Cesarean section rates and local resources for perinatal care in Japan: A nationwide ecological study using the national database of health insurance claims

Abstract: Higher elective CS rates might be associated with limited or unconsolidated medical resources. Policymakers should be aware of regional differences and the possible effects of perinatal care resources on CS rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 35 publications
4
27
1
3
Order By: Relevance
“…For example, the ID1 cannot follow up on patients who change their jobs and ID2 cannot follow up on patients who change their family names. The NDB has been used in several studies (Maeda et al 2018 ; Okumura and Nishi 2017 ; Okumura et al 2017 ). Our study protocol was reviewed and approved by the institutional review board at the Institute of Health Economics and Policy.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the ID1 cannot follow up on patients who change their jobs and ID2 cannot follow up on patients who change their family names. The NDB has been used in several studies (Maeda et al 2018 ; Okumura and Nishi 2017 ; Okumura et al 2017 ). Our study protocol was reviewed and approved by the institutional review board at the Institute of Health Economics and Policy.…”
Section: Methodsmentioning
confidence: 99%
“…The spontaneous surge in catecholamine secretion caused by uterine contractions is particularly important for fetal alveolar fluid clearance,12 and previous studies found that elective caesarean section before the onset of labour is a significant risk factor for TTN 3 13 14. The number of elective caesarean sections has increased in Japan over the last decades, and the caesarean section rate reached 11.5% in 2013 15. The elective caesarean section rate is expected to continue to increase due to increased maternal age,16 multiple gestations after fertility treatment17 and maternal request 18.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our previous report, the proportion of subjects born via CS in the R group of the present study was 25% (2 out of 8), while none were born via CS in the NR group (0%, n = 4) or the HC group (0%, n = 11). Although this difference did not reach statistical significance, the frequency of CS delivery in the R group was higher than that of general population in Japan [35]. Therefore, one reason for gut microbiota dysbiosis in the relapsing INS patients in the current study may relate to birth via CS.…”
Section: Discussionmentioning
confidence: 42%